2011
DOI: 10.1021/nn203165z
|View full text |Cite
|
Sign up to set email alerts
|

Folate-Targeted Polymeric Nanoparticle Formulation of Docetaxel Is an Effective Molecularly Targeted Radiosensitizer with Efficacy Dependent on the Timing of Radiotherapy

Abstract: Nanoparticle (NP) chemotherapeutics hold great potential as radiosensitizers. Their unique properties, such as preferential accumulation in tumors and their ability to target tumors through molecular targeting ligands, are ideally suited for radiosensitization. We aimed to develop a molecularly targeted nanoparticle formulation of docetaxel (Dtxl) and evaluate its property as a radiosensitizer. Using a biodegradable and biocompatible lipid-polymer NP platform and folate as a molecular targeting ligand, we engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(106 citation statements)
references
References 36 publications
5
101
0
Order By: Relevance
“…Indeed, preclinical studies have suggested that NP therapeutics are more effective than small molecule chemotherapeutics in chemoradiotherapy. 8, 1113 …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, preclinical studies have suggested that NP therapeutics are more effective than small molecule chemotherapeutics in chemoradiotherapy. 8, 1113 …”
Section: Introductionmentioning
confidence: 99%
“…19,20,23–25,28,36,48,49 The degree of DNA damage caused by chemotherapy and/or CRT can be quantified by γ -H2AX immunohistochemistry stain, a biomarker for DNA double-strand breaks. As shown in Figure 10, the administration of Wtmn NPs did not trigger any significant DNA damage compared with the control group.…”
Section: Resultsmentioning
confidence: 99%
“…The surge of interest in dendrimers was marked by Tomalia's finding in the mid-1980s (Werner et al 2011). Since then, the use and complexity of dendrimers has evolved at an impressive rate (Tomalia et al 1985;Malik et al 1999Malik et al , 2000.…”
Section: Dendrimersmentioning
confidence: 99%